Fetal Bone Marrow‐Derived Mesenchymal Stem/Stromal Cells Enhance Humanization and Bone Formation of BMP7 Loaded Scaffolds. Issue 12 (25th September 2017) - Shafiee, Abbas; Baldwin, Jeremy G.; Patel, Jatin; Holzapfel, Boris M.; Fisk, Nicholas M.; Khosrotehrani, Kiarash; Hutmacher, Dietmar W.
Abstract : Tissue engineered constructs built with human cells capable of generating a bone‐like organ within the mouse have attracted considerable interest over the past decade. Here, we aimed to compare the utility of human mesenchymal stem/stromal cells (MSC) isolated from fetal term placenta (fPL‐MSC) and fetal first trimester bone marrow (fBM‐MSC) in a polycaprolactone scaffold/BMP7‐based model in nude mice. Furthermore, fPL‐MSC were co‐seeded with fetal placenta‐derived endothelial colony forming cells (ECFC) to assess the impact of ECFC on fPL‐MSC osteogenesis. X‐ray radiography and micro computed tomography analyses showed enhanced bone formation in all BMP7 groups; however there was no difference after 2 months in bone formation between scaffolds seeded with fPL‐MSC alone or combination of ECFC and fPL‐MSC. Of interest, fBM‐MSC showed the highest level of bone formation. Additionally, endochondral ossification contributed in generation of bone in fBM‐MSC. Histological analysis showed the primary role of BMP in generation of cortical and trabecular bone, and the recruitment of hematopoietic cells to the scaffolds. Current in vivo engineered bone organs can potentially be used for drug screening or as models to study bone tissue development in combination with haematopoiesis. Abstract : A tissue engineered bone is generated using human stem cells, bone morphogenetic protein, and 3D printed medical grade polycaprolactone scaffold in a mouse model. Current in vivo engineered bone organs can potentially be used for drug screening or as models to study bone tissue development. This article is part of an AFOB (Asian Federation of Biotechnology) Special issue. To learn more about the AFOB, visitwww.afob.org .